Tinjauan Hukum Keluarga Islam Terhadap Tradisi Ngakuk Salah dalam Perkawinan Adat Komering di Kabupaten Ogan Komering Ulu Timur Sumatera Selatan - Taufiq Fauzi; Zuhraini; Iskandar Syukur (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Weddings in the Komering tradition have many processions starting from before the wedding to after the wedding. One of Komering's traditional traditions is to confess falsely. Ngakuk Salah is taking a woman with the condition of giving her juadah (glutinous rice cake). The tradition of admitting one's mistakes has been around since ancient times. Most people don't know when the ngakuk salah tradition existed, because this tradition is inherited from their ancestors, they still carry out this tradition even though the ngakuk salah tradition in its implementation is not like marriage in general. The problems observed in this research are how the practice of the ngakuk wrong tradition in Komering traditional marriages in Ogan Komering Ulu East Regency, South Sumatra, what is the impact of the ngakuk wrong tradition in Komering traditional marriages in Ogan Komering Ulu East Regency, South Sumatra and a review of Islamic family law on the ngakuk tradition wrong in traditional Komering marriages in East Ogan Komering Ulu Regency, South Sumatra. The method used is a qualitative method, namely a method of producing descriptive data. Researchers use data collection including: observation, interviews, and documentation. Based on field findings, the conclusion of this research is that the first traditional practice of ngakuk is wrong in Komering traditional marriages in East Ogan Komering Ulu Regency, namely rasan tuha (negotiation of certainty). Second, determine the certainty of wrongdoing by the male family by bringing ½ can of juadah (sticky rice cake) or 7.5 kg. The third implementation of ngakuk salah is at the man's residence and is carried out on the main road until the wedding ceremony is finished. The impact of the tradition of confessing wrongly in traditional Komering marriages in East Ogan Komering Ulu Regency is that if a married woman cannot receive inheritance and adoq from her parents. Another impact that occurs from this wrongful marriage is that there is no longer any family relationship or position of the children to their parents and if the husband and wife have divorced or are divorced according to customary law then they are allowed to return to their families. This review of Islamic family law regarding the practice of wrongful confession traditions in Komering traditional marriages in East Ogan Komering Ulu Regency does not conflict with Islamic religious norms and customary law because it must still follow the rules in Islamic law as well as in customary law.